A distributed double-layer control algorithm for medium voltage regulation and state of charge consensus of autonomous battery energy storage systems in distribution networks - Parada Contzen, Miguel (Journal of energy storage, 2024)
The increasing integration of Distributed Generation (DG) based on Renewable Energy Sources (RES) in traditional distribution systems necessitates the adoption of smart grid strategies. These strategies rely heavily on energy storage actuation to manage the inherent variability of RES and ensure autonomous operation. This article presents a hierarchical digital control strategy for managing distribution power systems, utilizing Battery Energy Storage Systems (BESS) to regulate voltage amplitude and enhance overall behavior for efficient energy management. At the primary control level, operating at a minute-scale actuation rate, an integral voltage regulation loop determines the BESS power injection or consumption, refined by a fuzzy conditioning of signals that accounts for the state of charge and operational modes of each device. Laplacian and random switching secondary consensus control strategies, operating at a slower rate, ensure coordinated action among individual units. The convergence of these strategies is analytically validated using Lyapunov’s theory under idealized conditions. Extensive dynamic simulations over a 24-hour period demonstrate the proposed strategy’s effectiveness in improving power quality and coordinating voltage regulation, particularly in terms of enhancing the power factor and reducing the standard deviation of voltage and power variables over time in a coordinated manner. •Distribution networks with distributed generation and battery energy storage systems.•Primary level voltage regulation at nodes with BESS.•Secondary level consensus coordination of BESS states of charge.•Distribution grid control as functional unit in smart grid environment.